Libri. - Anker, Jean, 1892-1957; International Federation of Library Associations; International Federation of Library Associations (Copenhagen, Munksgaard., 1950)
Vols. 4-<24> include Communications of the International Federation of Library Associations (IFLA-FIAB).
Vols. for <2008-> published: München : K. G. Saur Verlag, an imprint of Walter de Gruyter GmbH & Co.--C.f. Journal's website (piece not in hand).
"International library review"--varies.
Editor: 1950-<54> J. Anker.
Keywords: FEDERACION INTERNACIONAL DE ASOCIACIONES DE BIBLIOTECARIOS -- PUBLICACIONES PERIODICAS; Library science -- Periodicals; BIBLIOTECOLOGIA -- PUBLICACIONES PERIODICAS; Documentaire informatie; IFLA